Case of acute severe postpartum urinary incontinence: an extravesical subsphincteric prolapsed ureterocoele. (12th January 2018) - Seth, Jai H; Walker, Roger
Abstract : A 32-year-old woman presents to outpatients 10 days postpartum, with symptoms of an intermittent vaginal lump and urinary incontinence. Vaginal examination revealed no demonstrable prolapse or stress incontinence. A swelling in the bladder was noted during an antenatal scan suggesting a ureterocoele. She was referred for pelvic floor physiotherapy in the first instance. Forty-eight hours later, she represented to casualty with discomforting vaginal lump symptoms and continuous urinary incontinence. At this stage on vaginal inspection, there was an evident dusky lump emerging from the urethra with continuous incontinence. An extravesical subsphincteric prolapsed ureterocoele was evident, 5 cm beyond the external urethral meatus. The diagnosis was confirmed with an MRI scan which demonstrated the prolapsed obstructing ureterocoele causing significant left-sided hydroureteronephrosis. The ureterocoele was managed with a cystoscopy and transurethral incision of the ureterocoele under anaesthesia, which facilitated drainage and resolution. At 3-month postoperatively, the patient remains continent and satisfied.